Vitamin D supplementation in pregnancy: A word of caution. Familial hypercalcaemia due to disordered vitamin D metabolism. (March 2020) - Macdonald, Christy; Upton, Thomas; Hunt, Penny; Phillips, Ian; Kaufmann, Martin; Florkowski, Chris; Soule, Steven; Jones, Glenville
Disorders of vitamin D metabolism have only recently become more widely recognized. In 2011, a series reported six children with familial idiopathic infantile hypercalcaemia, a condition in which patients develop hypercalcaemia following bolus vitamin D supplementation due to mutations in CYP24A1, formerly known as 24-hydroxylase. This is the chief enzyme in the catabolism of 1, 25-dihydroxyvitamin D3 (calcitriol) to inactive 1, 24, 25-(OH)3 D3 . Isolated cases of loss of function CYP24A1 mutations have been reported across a wide spectrum of ages, including three cases first identified during pregnancy in the context of vitamin D supplementation. We describe a family in which two siblings had hypercalcaemia due to a disorder of calcitriol catabolism as a result of compound heterozygous loss of function mutations of CYP24A1, including a novel mutation K351Nfs*21. The index case, who has kindly given written informed consent for this report, was a female in her mid-20s presenting with symptomatic hypercalcaemia precipitated by vitamin D supplementation in her first pregnancy. In a subsequent pregnancy, she remained normocalcaemic in the absence of supplementation. Her asymptomatic brother was identified through cascade screening. Upregulation of calcitriol production in pregnancy, particularly when combined with vitamin D supplementation, can unmask previously unidentified disorders of vitamin D metabolism. This report emphasizes the importance of screening of family members and the need for caution with vitamin D supplementation in pregnancy.